2022
DOI: 10.1038/s41598-022-11457-5
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable film based on cellulose and thiazolidine bearing UV shielding property

Abstract: The current rationale is exploring new eco-friendly UV- shielding films based on cellulose and thiazolidine. Cellulose was oxidized to dialdehyde cellulose (DAC) and tricarboxy cellulose (TCC) by periodate and TEMPO/periodate/hypochlorite, respectively. While E-3-amino-5-(phenyldiazenyl)-2-thioxothiazolidin-4-one (TH) was synthesized by coupling diazonium salt with the 5-methylene of 2-thioxo-4-thiazolidinone. DAC was then coupled with TH via Schiff base reaction and incorporated onto TCC with different ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…6). The studies found that the film with 10% Dialdehyde cellulose-E-3-amino-5-(phenyldiazenyl)-2thioxothiazolidin-4-one has 99.99%, 99.88%, and 96.19% UV-A, UV-B, and ultraviolet protection factor (UPF), respectively [56].…”
Section: Ligninmentioning
confidence: 99%
“…6). The studies found that the film with 10% Dialdehyde cellulose-E-3-amino-5-(phenyldiazenyl)-2thioxothiazolidin-4-one has 99.99%, 99.88%, and 96.19% UV-A, UV-B, and ultraviolet protection factor (UPF), respectively [56].…”
Section: Ligninmentioning
confidence: 99%
“…Nanocrystalline cellulose is a rod-shaped particle with an excellent aspect ratio, with a width of approximately 5–30 nm and a length of approximately 100–500 nm [ 105 ]. It also has superior axial Young’s modulus, high specific surface area, high transparency, and a number of other excellent properties, References [ 106 , 107 ]. As a result, nanocrystalline cellulose is widely used not only in drug delivery but also in many fields, such as papermaking, food production, and electronics [ 108 , 109 , 110 ].…”
Section: Biopolymers and Their Application In Renal Diseasesmentioning
confidence: 99%
“…Pharmaceutics 2023, 15, x FOR PEER REVIEW 10 of 18 [105]. It also has superior axial Young's modulus, high specific surface area, high transparency, and a number of other excellent properties, References [106,107]. As a result, nanocrystalline cellulose is widely used not only in drug delivery but also in many fields, such as papermaking, food production, and electronics [108][109][110].…”
Section: Cellulosementioning
confidence: 99%